How to Increase the Quality of Accounting Information System and Accounting Information Quality in Bandung’s Higher Educations? - Annisa Fitri Anggraeni; Deden Komar Priatna; Winna Roswinna; Eprianus Zai (Greenation Research & Yayasan Global Resarch National, 2023)
The existence of information becomes a very important part for individuals. The process of processing data into information is the main activity carried out by each individual. The process of processing data into information provides benefits not only for individuals, but also for organizations. Information is crucial for individuals and organizations. Information plays an important role in all aspects of life, both individuals and organizations. This study aims to determine the effect of information technology and organizational structure on the quality of accounting information systems and the effect of the quality of accounting information systems on the quality of accounting information at universities in Bandung. The population of this research is all universities in Bandung, with a sample of 30 universities with 3 observation units from each university. The research results are processed using the SEM-PLS approach with the help of the Wrap-PLS application. The results of the study came from 28 universities with a questionnaire return rate of 78 respondents, showing the results that there is an influence between information technology and organizational structure on the quality of accounting information systems and there is an influence between the quality of accounting information systems on the quality of accounting information.